HUBUNGAN ANTARA GAYA KEPEMIMPINAN PATH GOAL SUPERVISOR PABRIK BAJA DENGAN TINGKAT KEPATUHAN SOP (STANDARD OPERATIONAL PROCEDURE) PEKERJA - Wahyu Fahrul Ridho (Universitas Airlangga, 2015)
ABSTRACTEmployee ignorance on Standard Operational Procedures (SOP) is one of the main causes of workplace accidents. This study was conducted to analyze the correlation between path goal leadership implemented by Gresik steel factory supervisors and employee obedience on company SOP. This study applied quantitative approach and cross-sectional research design. The data were collected through observation and interview on 52 respondents consisting of employees working led by 4 different supervisors. Systematic random sampling is used for sampling method. In-depth interviews were conducted to gain more information regarding the variables analyzed in this study. The independent variables analyzed in this study were path goal leadership style implemented by the supervisors and the dependent one is SOP obedience. This study found that employee obedience level on company SOP of each working units is 86% for drilling unit; 78.57% for marking and cutting unit; 100% for assembly unit; and 41.67% on painting unit. The results of Spearman correlation test indicated that path goal leadership style implemented by the supervisors significantly correlated with obedience level of the employees on company SOP with p < 0.05. there were positive correlation among the variables with correlation coefficient 0.416 (p = 0.001). Based on these findings, it could be concluded that the better path goal leadership style implementation made by the supervisors the higher employee obedience level on company SOP.Keywords: leadership style, Path Goal Theory, SOP obedience, occupational safety